Certified nursing assistants as agents of creative caregiving in long‐term care. (7th October 2019) - Eaton, Jacqueline; Cloyes, Kristin; Paulsen, Brooke; Madden, Connie; Ellington, Lee
Abstract: Aim: Certified nursing assistants (CNAs) provide most of the direct care for long‐term care (LTC) residents, yet there are few CNA‐led interventions aimed at improving quality of care. In our preliminary work developing a CNA art‐based intervention, we describe CNA definitions and perceptions of creativity in relation to care of LTC residents. Methods: Data from six sequential focus groups with CNAs ( n = 14) in two LTC facilities were analysed to describe the concept of creativity in relation to LTC caregiving and its meaning to CNAs working in LTC. Results: Certified nursing assistants defined creativity as formal art‐making, yet they also described creative approaches to engaging residents in order to build relationships and reduce challenging behaviour. While most linked creativity with discerning and responding to resident needs, creativity was also foundational to time management, teamwork and navigating challenges. Conclusion: Developing CNA‐centred interventions to promote creative caregiving may enhance both person‐centred LTC and CNA empowerment, improving resident care. Implications for practice: CNA creativity should be viewed as a skill with the potential to enhance care and increase CNA empowerment. Interventions should be developed, in partnership with CNAs, to promote creative caregiving.